Product Binary L-Cordial Labeling of Various Degree Splitting Graphs - Prajapati, U. M.; Patel, P. A. (Communications in Mathematics and Applications, 2024)
This study examines the probability of the degree splitting operation results from various graphs being product binary \(L\)-cordial graphs. The graphs under investigation include the path graph \((P_n)\), comb graph \((P_nk_1)\), double comb graph \((P_n2k_1)\), cycle graph \((C_n)\), shell graph \((S_n)\) and ladder graph \((L_n)\). The application of product binary \(L\)-cordial labelling demonstrates that these analyzed graphs exhibit characteristics of product binary \(L\)-cordial graphs.